Delayed effect of dry-land strength training sessions on swimming performance - Tsoltos, A.; Arsoniadis, G.; Tsolakis, C.; Koulouvaris, P.; Simeonidis, T.; Chatzigiannakis, A.; Toubekis, A. (Journal of Functional Morphology and Kinesiology, 2023)
The purpose of the study was to examine the effects of dry-land strength endurance (SE) and maximum strength (MS) sessions on next-day swimming performance. Eight swimmers (age: 18.6 ± 2.9 years) performed evening training sessions (19:00-19:40), including: (i) SE (2 × 15 - 20 repetitions, 50% of 1-RM), (ii) MS (2 × 5 repetitions, 90% of 1-RM), (iii) control (CON: no dry-land training). All sessions were followed by a 90-min swimming training (20:00-21:30). Medicine ball throw and countermovement jump, free countermovement jump and squat jump were evaluated before and after the dry-land training session and 12 h later, before a 100-m front crawl sprint (next day at 8:30 a.m.). Performance time, RPE, blood lactate and biomechanical variables in 100-m sprint were no different between conditions (time, MS: 64.70 ± 7.35, SE: 63.81 ± 7.29, CON: 64.52 ± 7.71 s, p > 0.05). Jump height was not changed before and after dry-land and before the 100-m sprint in all conditions (p > 0.05). Medicine ball throw was lower in MS compared to CON before the 100-m sprint (MS: 4.44 ± 1.11, vs. CON: 4.66 ± 1.21 m, p < 0.05). Upper-body but not lower- body muscle function may be affected by MS training. However, performance in a 100-m test is not affected by dry-land training performed 12 h earlier.